Flyway connectivity and population status of the Greylag Goose Anser anser in East Asia - Yan, Ming; Yi, Kunpeng; Zhang, Junjian; Batbayar, Nyambayar; Xu, Zhenggang; Liu, Guanhua; Hu, Binhua; Zheng, Bofu; Antonov, Aleksei; Goroshko, Oleg; et al. (Wildfowl, 2020)
European populations of the Greylag Goose Anser anser have been studies for over 50 years, but those in the East Asian flyway are less well known. Here we describe the breeding and wintering distribution of Greylag Geese wintering in China, based on historical and newly-reported telemetry data (from 31 individuals contributing complete migrations), wintering waterbird surveys and expert knowledge. Historical records, and also the data presented here, indicate that Greylag Geese breeding in the north of the Xinjiang Uygur Autonomous Region, China, and in Mongolia east of 93Â°E, through Inner Mongolia to western parts of Heilongjiang Province, China, likely almost all winter east of 107Â°E in China (97% in the Yangtze River floodplain and 3% in the Yellow River floodplain). Annual mid-winter waterbird counts confirm that very few Greylag Geese winter in Japan and South Korea. Count data suggest that the Far East Asia Greylag population wintering in China currently numbers 30,000 individuals, a major increase compared to 3,263 counted in 2005. Historical records however indicate that the wintering distribution was far greater 30 years ago, and that Greylag Geese are now less common than previously in Guangdong, Guizhou, Hainan, Henan, Hunan, Anhui and Jiangsu Provinces, as the species has become more concentrated further north in the Yangtze and Yellow River floodplains. On the basis of count data from winters 2010/11â€“2019/20, we identified 21 current key wintering sites (holding â‰¥ 1% of the flyway population, i.e. 300 birds) in the Yangtze River floodplain and one in the Yellow River floodplain for this population. Increasing use of farmland in winter, as well as site protection and sympathetic local management of wintering sites may have contributed to recent increases in Greylag Goose abundance in the flyway. These results provide a more robust basis for assessing the current status of the Far East Asia Greylag Goose population and a guide to priorities for further internationally coordinated research of the species.Â The need to improve monitoring and habitat management for maintaining the increasing numbers wintering in China is also emphasiseduropean populations of the Greylag Goose Anser anser have been studies for over 50 years, but those in the East Asian flyway are less well known. Here we describe the breeding and wintering distribution of Greylag Geese wintering in China, based on historical and newly-reported telemetry data (from 31 individuals contributing complete migrations), wintering waterbird surveys and expert knowledge. Historical records, and also the data presented here, indicate that Greylag Geese breeding in the north of the Xinjiang Uygur Autonomous Region, China, and in Mongolia east of 93Â°E, through Inner Mongolia to western parts of Heilongjiang Province, China, likely almost all winter east of 107Â°E in China (97% in the Yangtze River floodplain and 3% in the Yellow River floodplain). Annual mid-winter waterbird counts confirm that very few Greylag Geese winter in Japan and South Korea. Count data suggest that the Far East Asia Greylag population wintering in China currently numbers 30,000 individuals, a major increase compared to 3,263 counted in 2005. Historical records however indicate that the wintering distribution was far greater 30 years ago, and that Greylag Geese are now less common than previously in Guangdong, Guizhou, Hainan, Henan, Hunan, Anhui and Jiangsu Provinces, as the species has become more concentrated further north in the Yangtze and Yellow River floodplains. On the basis of count data from winters 2010/11â€“2019/20, we identified 21 current key wintering sites (holding â‰¥ 1% of the flyway population, i.e. 300 birds) in the Yangtze River floodplain and one in the Yellow River floodplain for this population. Increasing use of farmland in winter, as well as site protection and sympathetic local management of wintering sites may have contributed to recent increases in Greylag Goose abundance in the flyway. These results provide a more robust basis for assessing the current status of the Far East Asia Greylag Goose population and a guide to priorities for further internationally coordinated research of the species.Â The need to improve monitoring and habitat management for maintaining the increasing numbers wintering in China is also emphasised.